Prevalence, perceptions and predictors of complementary and alternative medicine (CAM) use in selected communities in the Philippines - Dahilig, Vina Rose A. 1982-
The study examines the differences in the prevalence, perceptions and predictors of use of complementary and alternative medicine among residents of selected rural and urban communities in the Philippines using the CAM Healthcare Model. Interviews were conducted on 146 participants in Batangas, Caloocan and Paranaque using a structured questionnaire that applies the RAND Short Form (SF) 36 and the Brief Illness Perception Questionnaire as measures of self-perceived health status. A higher prevalence was observed among the rural respondents (68.4%) as compared with their urban counterparts (51.5%). Users in both rural and urban areas perceived CAM as beneficial. Significant predictors of use included the type of community, an annual income of less than PhP450,000.00, more than 10 years of residence in the community, self-perceived health status in the Energy/Fatigue, Emotional Well-being and Pain scales in the SF 36, presence of chronic illness, and consultations to traditional faith healer for health issues. Since only about 27% of the variability in the odds of using CAM can be explained by the model, further studies investigating other predictors of use and identifying confounding variables are recommended.